Sustainable Competitive Advantage of Indonesian Traditional Salt: A PRISMA-Based Literature Review - Roudlotul Badi'ah; Imtinan Widhah Kumala; Armen Zulham; Nilam Hemalia Putri; Lisa Oktavia Anggraini (Goodwood Publishing, 2026)
Purpose: This study aims to identify the main driving and inhibiting factors contributing to the sustainable competitive advantage of Indonesian traditional salt and propose practical strategies for improvement. As the first PRISMA-based systematic review of Indonesian salt competitiveness, it provides an integrated and evidence-based synthesis to strengthen the sector’s sustainability and resilience. Research Methodology: This research employs a systematic literature review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines, based on 22 selected articles from the Dimensions database. The review was conducted in four stages: design, implementation, analysis, and writing. Results: The study identified six driving factors community empowerment, economic aspects, environmental conditions, policy support, production technology, and product quality and differentiation and seven inhibiting factors, including climate dependence, economic pressures and imports, environmental pollution, limited technology and infrastructure, low quality and standards, socio-demographic marginalization, and weak marketing and institutional capacity. To address these issues, seven strengthening strategies are proposed, focusing on quality improvement, marketing efficiency, sustainable environmental management, institutional and financial empowerment, green entrepreneurship, risk management, and household economic contribution. Conclusions: Integrating technological, institutional, ecological, and socio-economic aspects can enhance salt quality, empower local farmers, advance the national blue economy agenda, and reduce import-dependence. Limitations: The evidence was drawn from secondary sources published in 2025 within the Dimensions database; therefore, generalization is limited. Contributions: This study presents the first integrated PRISMA-based framework of drivers, barriers, and strategies to support researchers, policymakers, and practitioners in enhancing the competitiveness of traditional Indonesian salt.